Economic and Parametric Approach to the Creation and Functioning of the Advertising Project - KUZMINSKA, Yuliia M.; YEVTUKHOVA, Tetiana O.; VASYLKONOVA, Elina O.; BEDRII, Dmytro I.; RIEPNOVA, Tetiana P.; ZAKHARCHENKO, Oleg V. (Journal of Advanced Research in Law and Economics, 2020)
Today, development is an integral part of the life of any company, including advertising. A distinctive feature of project-oriented companies is that they implement development activities through projects and programs, as well as apply a project approach to the implementation of current production advertising activities. Speaking of advertising, one should not forget that in the event of advertising on computer networks has become commonplace. Network advertising is not inferior to television, radio, or newspaper. With us, advertising on the networks is a new thing. In this study, it is accepted that during the entire life cycle, the advertising company/business develops either along the path of progress or the path of regression (the second half of the life cycle). For example, for a multidisciplinary company, some advertising businesses, reducing the size of existing advertising businesses, restructuring, etc., i.e. measures of regressive nature, can be aimed at positive qualitative changes – for better adaptation to the market, for higher competitiveness due to faster response to changes in the environment and etc. Thus, the entire life cycle of the company is a process of development, which is provided in the form of a sequence of advertising projects and programs of development of advertising business. And today, many companies, including the advertising industry, can be identified as project-oriented.